Prospect a short film that elevates the role of the parent in a senior high school student's career decision making process - Dy, Katherina Marie Therese C.
The study focused on identifying the social spheres of influence among students in senior high school, as well as aimed to understand the role these influences play in the student's life. The findings of this research was used to determine how well they perceive the concept of vocational maturity. The method in which was executed in order to attain the qualitative data was a series of five (5) semi-structured interviews with working adults in order to garner personal insight on the achievement of vocational maturity, as well as their career decision-making process. In addition, a focused group discussion with five (5) senior high school students followed in order to collect an overall understanding of the different social spheres that influenced their decisions and perception of vocational maturity. The results were analyzed by finding commonalities in the answers of the participants, as well as recurring insights. The findings of the study show that parents, family and peers are major spheres of influence among high school students and are constructed by the Filipino culture, as well as their high probability of achieving vocational maturity at a young age with the help of the new K-12 schooling organizational system. Moreover, this study also analyzed the factors that may contribute to the achievement of vocational maturity to aid the younger generation with more knowledge on how to do so.